Treatment of a Textile Effluent by Electrochemical Oxidation and Coupled System Electooxidation–Salix babylonica - Alejandra Sánchez-Sánchez; Moisés Tejocote-Pérez; Rosa María Fuentes-Rivas; Ivonne Linares-Hernández; Verónica Martínez-Miranda; Reyna María Guadalupe Fonseca-Montes de Oca (International Journal of Photoenergy)
The removal of pollutants from textile wastewater via electrochemical oxidation and a coupled system electrooxidation—Salix babylonica, using boron-doped diamond electrodes was evaluated. Under optimal conditions of pH 5.23 and 3.5 mA·cm−2 of current density, the electrochemical method yields an effective reduction of chemical oxygen demand by 41.95%, biochemical oxygen demand by 83.33%, color by 60.83%, and turbidity by 26.53% at 300 minutes of treatment. The raw and treated wastewater was characterized by infrared spectroscopy to confirm the degradation of pollutants. The wastewater was oxidized at 15-minute intervals for one hour and was placed in contact with willow plants for 15 days. The coupled system yielded a reduction of the chemical oxygen demand by 14%, color by 85%, and turbidity by 93%. The best efficiency for the coupled system was achieved at 60 minutes, at which time the plants achieved more biomass and photosynthetic pigments.